53 Abnormal myocardial strain in adult patients with unrepaired ebsteins anomaly and prediction of impaired exercise tolerance. (June 2018) - Dardeer, Ahmed; Hudsmith, Lucy; Liu, Boyang; Wesolowski, Roman; Steeds, Richard
Abstract : Introduction: Morbidity and mortality in unrepaired Ebstein's anomaly (EA) relate to exercise capacity, ventricular dysfunction and congestive cardiac failure. Accurate assessment of ejection fraction is difficult due to geometry of the ventricles and complex anatomy of the tricuspid valve in these patients. Myocardial deformation detects ventricular function before other parameters in other cardiovascular disease and has incremental value in predicting outcome but has not been tested in EA. Objectives: 1. To compare myocardial deformation in adult patients with unrepaired EA with control subjects; 2. To investigate the relationship with exercise capacity as a known predictor of outcome in these patients measured using cardio-pulmonary exercise testing (CPEX). Methodology: This is a single, centre study of 36 consecutive patients with unrepaired EA (20 females) aged 36.3±13.2 years undergoing cardiovascular magnetic resonance (CMR; 1.5T Avanto, Siemens). 2D RV longitudinal strain (RV GLS) and 3D left ventricular longitudinal (GLS) and circumferential (GCS) strains were obtained using Circle cvi42 (Calgary, Canada). Strain values were compared with normative data obtained from age and sex matched healthy controls using paired samples t test. Pearson correlation was used to study the correlation between strain and cardiopulmonary exercise measures. Results: Demographic data and conventional CMR data in EA and controls are displayed in table 1. RV end diastolic volume was increased in EA and the RV and LV ejection fraction were impaired compared to the healthy controls. RV GLS and RA GLS were impaired in EA compared to control subjects, as were LV GLS and GCS (see figure 2). RA peak strain correlated with% predicted VO2 peak (r=−0.472, p=0.017), peak VO2 (r=−0.431, p=0.028) and VE/VCO2 slope (r=0.414, p=0.036 respectively). There was no correlation between severity of tricuspid regurgitation, RV ejection fraction or any RV strain parameters and CPEX parameters. Conclusion: In adult patients with unrepaired EA, RV, RA and LV global strains are impaired compared to controls. Functional RA peak strain is related to impaired exercise capacity and future study is needed to establish whether these parameters have independent prognostic value in this cohort.